ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR: (Studi Kasus Pada Kantor Bersama Samsat Kab. Lamongan) - Zakaria Anshori (STIE Mahardhika, 2020)
This study aims to analyze the influence of tax service quality variables, special services, sanctions and the use of information technology on motor vehicle taxpayer compliance in the Joint Office of Lamongan Regency. The independent variables in this study are the quality of tax services, tax authorities, tax sanctions, and the use of information technology. The dependent variable is taxpayer compliance. The research uses survey method by giving questionnaires to taxpayer registered in the office along with Samsat District Lamongan sample determination was done by accidental sampling method and than collected data were analyzed by multiple linear regression. The number of samples in this study were 110 respondents. The results of this study indicate and simultaneously that the quality of tax service, tax service, tax sanctions, utilization of information technology significant effect on taxpayer compliance.